Evaluation of the Internal Control System over Raw Material Purchases at the BIG DONAT Cake Production MSME in Makassar - Annisa Nurul Fajri; Raihana; Siti Aisyah; Muchriana Muchran (www.amertainstitute.com, 2025)
This research aims to evaluate the internal control system for raw material purchases at MSME Big Donat in Makassar using the COSO (Committee of Sponsoring Organizations of the Treadway Commission) framework approach. This study is crucial as internal control plays a strategic role in ensuring operational effectiveness and efficiency, including the raw material purchasing process, which is a key factor in production. A descriptive qualitative approach was employed, with data collected through interviews. The primary informant in this study was the business owner. Data were analyzed based on the five main components of the COSO framework: control environment, risk assessment, control activities, information and communication, and monitoring. The findings indicate that the internal control system at MSME Big Donat is operational in practice but not yet fully compliant with COSO standards. The control environment is considered quite good, with an organizational structure and strong work ethic values; however, it is not yet supported by written standard operating procedures (SOPs) or job descriptions. Risk assessment is conducted directly by the business owner without formal documentation. Control activities, such as purchase authorization and goods inspection, are performed but lack standardized purchase forms and written procedures. Information and communication are carried out informally without a standardized recording system. Monitoring is conducted routinely by the owner but is not yet documented in the form of evaluation reports. This research provides a real-world illustration of internal control conditions in food-sector MSMEs and offers recommendations for improvement to MSME Big Donat in enhancing the effectiveness of its internal control system in accordance with COSO standards.